2022
DOI: 10.1111/pcmr.13025
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and melanoma: Implications for immunotherapy

Abstract: New therapies such as immune checkpoint blockers (ICB) have offered extended survival to patients affected by advanced melanoma. However, ICBs have demonstrated debilitating side effects on the joints, liver, lungs, skin, and gut. Several biomarkers have been identified for their role in predicting which patients better tolerate ICBs. Still, these biomarkers are limited by immunologic and genetic heterogeneity and the complexity of translation into clinical practice. Recent observational studies have suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Even though NLR and dNLR may appear similar at a glance, the dNLR may be more informative than NLR, because it includes monocytes as well as other granulocyte subpopulations, such as eosinophils. Recent observational investigations indicated that eosinophil counts and serum levels of the eosinophil cationic protein are significantly associated with prolonged survival in metastatic CM [32]. Finally, we acknowledge that our study presents two major limitations: (1) it is a retrospective study without a validation or control cohort and (2) the sample size included in this study was comprised of a small number of CM patients, possibly resulting in statistically insignificant results which could have likely been avoided using a larger study population.…”
Section: Discussionmentioning
confidence: 99%
“…Even though NLR and dNLR may appear similar at a glance, the dNLR may be more informative than NLR, because it includes monocytes as well as other granulocyte subpopulations, such as eosinophils. Recent observational investigations indicated that eosinophil counts and serum levels of the eosinophil cationic protein are significantly associated with prolonged survival in metastatic CM [32]. Finally, we acknowledge that our study presents two major limitations: (1) it is a retrospective study without a validation or control cohort and (2) the sample size included in this study was comprised of a small number of CM patients, possibly resulting in statistically insignificant results which could have likely been avoided using a larger study population.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our experiment where we observed an association between MAIT cell-mediated inhibition of MC38-derived tumors and an increase in tumor production of GM-CSF and eotaxin-1 production in the tumors. With eosinophils’ known ability to release effector molecules like major basic protein (MBP) into the tumor microenvironment to induce cancer cell lysis (55), these data support the involvement of eosinophils in MAIT-mediated tumor suppression.…”
Section: Discussionmentioning
confidence: 89%
“…There were also significant differences among studies concerning the association between eosinophilic granulocyte count and treatment response. Despite the extremely heterogeneous data, eosinophils could serve as a prognostic marker in immunotherapy of melanoma, given their effects on the TME and the relationship between TME and ICI-therapy response ( 27 , 57 ). In a retrospective cohort based on a pharmacovigilance registry that included 909 patients with various tumors receiving anti-PD-1 or anti-PD-L1 therapy, 2.8% of patients were found to have immune-related eosinophilia, the majority of whom were being treated for advanced melanoma ( 58 ).…”
Section: Discussionmentioning
confidence: 99%